Reply—On Stationarity and Optimality in Arborescent Production/Inventory Systems - Graves, Stephen C.; Schwarz, Leroy B. (Management Science, 1978)
We are indebted to Jack Muckstadt and Howard Singer for calling our attention to two errors in [Graves, S. C., Schwarz, L. B. 1977. Single cycle continuous review policies for arborescent production/inventory systems. Management Sci. 23 (5, January) 529–540.].